ANALYSIS OF CUSTOMER SATISFACTION CASE STUDY IN OMI MINIMARKET YOGYAKARTA - Wele, Valentina; Darini, M.Si., Dra. Sri; N., SE., MM., Winanto (Management, 2010)
The purpose of this study was to analyze the correlation factor product, price, promotion, location and service employees who are influential on the level of consumer satisfaction in Omi Minimarket located at Wonocatur Banguntapan Bantul, Yogyakarta. The formulation of the problem in this research is to know whether the factors product, pricing, promotion, location and service employees and Which factors most affect the level of satisfaction Omi Minimarket consumers on Yogyakarta. The samples in this study using the technique of incidental sampling. Incidental sampling is a sampling technique based on needs, namely those who by chance met the researcher can used as a data source. The rationale for incidental sampling method is because the number of population is not known for certain. Based on the method sampling is determined the number of samples in this study as many as 100 people. Results of testing hypotheses simultaneously and partially show significant relationship of the variables product, price, promotion, location and service employees, to the level of consumer satisfaction in Omi Minimarket Yogyakarta. The coefficient of determination showed the product variable has a relatively large effect among other variables for 0.199. Keywords: Level of consumer satisfaction, service, product, price, promotion